A turtle population study in an isolated urban wetland complex in Ontario reveals a few surprises - Marc Dupuis-Désormeaux; Vince D'Elia; Ryan Burns; Brittany White; Suzanne E. MacDonald (Canadian Science Publishing, 2019)
We report on the results of the first mark-recapture survey of freshwater turtles in an isolated urban wetland complex in one of Canada's fastest growing municipalities. Although we found turtles in every surveyed wetland, the density and assemblage of turtles in smaller wetlands were significantly different than in larger wetland bodies. We also documented two species of turtles that were thought to be absent from this wetland complex, the Northern Map turtle and Eastern Musk turtle. We noted that a wetland that was bisected by a high-traffic road showed a male-skewed sex ratio in the population of Midland Painted turtles but not in the population of Eastern Snapping turtles. As a whole, the sex ratios inside the wetland complex were not skewed. These results reinforce the conclusions of a previous study of a single wetland within this same complex that had found a correlation between road mortality and a male-skewed sex ratio in Midland painted turtles. We discuss population sources and sinks within the complex and the importance of protecting the overland corridors that support the safe turtle movements within this provincially significant wetland complex.